Sintered body and cutting tool
By using diamond particles of specific concentration and particle size and sintered bodies of bonded materials in the cutting tool tip, specific compounds are precipitated from the combined materials, the tool life and friction plasma problems are solved, and higher wear resistance is achieved and oxidation resistance.
Patent Information
- Application Number
- CN202280096151.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-25
- Publication Date
- 2024-12-17
AI Technical Summary
When the existing sintered bodies are used in cutting tools, there is room for improvement in the tool life, and it is difficult to effectively suppress the generation of friction plasma, resulting in accelerated wear.
Using sintered bodies of diamond particles and bonded materials, the boron concentration in diamond particles is 0.001% or less, and the boron concentration in bonded materials is 0.01% or less, and the compound such as Co22B4C2 and W2Co21B6 are precipitated in the tip of the knife. , W2Co2B6, etc., adjust the peak intensity through X-ray diffraction to ensure that the resistivity is below 3.0Ω·cm, the average particle size of diamond particles is above 0.5μm or more and 50μm, and the proportion is above 80% or less than 99%.
It significantly improves the tool life, improves the wear resistance and oxidation resistance of the cutting edge part, inhibits the generation of friction plasma, and extends the service life of the cutting edge part.
Smart Images

Figure CN119156360A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a sintered body and a cutting tool. Background Art
[0002] Patent Document 1 (Japanese Patent Application Laid-Open No. 2008-133172) describes a sintered body. The sintered body described in Patent Document 1 is formed by mixing diamond powder doped with boron and carbonate powder, and heating and pressurizing the mixture.
[0003] Patent document 2 (Japanese Patent Application Laid-Open No. 58-199777) describes a sintered body. The sintered body described in Patent document 2 is formed by mixing diamond powder and catalyst metal powder, and heating and pressurizing the mixture. In addition, the catalyst metal powder includes boron carbide added powder and metal powder (iron, nickel, cobalt, etc.).
[0004] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2008-133172 Patent Document 2: Japanese Patent Application Laid-Open No. 58-199777 Summary of the invention The sintered body disclosed in the present invention comprises diamond particles and a bonding material. The boron concentration in the diamond particles is 0.001 mass percent or more and 0.1 mass percent or less. The boron concentration in the bonding material is 0.01 mass percent or more and 0.5 mass percent or less. BRIEF DESCRIPTION OF THE DRAWINGS
[0005] Figure 1 is a top view of the cutting insert 100 .
[0006] Figure 2 is a perspective view of the cutting insert 100 .
[0007] Figure 3 It is a process diagram showing a method for manufacturing a sintered body constituting the blade tip portion 20 . DETAILED DESCRIPTION
[0008] [Problems to be Solved by the Present Disclosure] The inventors of the present invention have conducted intensive research and found that there is room for improvement in tool life when the sintered bodies described in Patent Document 1 and Patent Document 2 are used in cutting tools. The present disclosure provides a sintered body capable of improving tool life when used in cutting tools.
[0009] [Effects of the present disclosure] According to the sintered body of the present disclosure, when applied to a cutting tool, it is possible to improve the tool life.
[0010] [Description of Embodiments of the Present Disclosure] First, embodiments of the present disclosure will be described by way of examples.
[0011] (1) A sintered body according to one embodiment includes diamond particles and a binder. The boron concentration in the diamond particles is 0.001 mass percent to 0.1 mass percent. The boron concentration in the binder is 0.01 mass percent to 0.5 mass percent.
[0012] According to the sintered body of the above (1), when applied to a cutting tool, the tool life can be improved.
[0013] (2) In the sintered body of (1) above, a boron concentration in the binder may be 0.05 mass % or more and 0.5 mass % or less.
[0014] (3) The sintered body of (1) or (2) may further include a compound precipitated in the binder. The compound may contain at least two of cobalt, boron and carbon. The value obtained by dividing the peak intensity of the compound by the peak intensity of diamond when performing X-ray diffraction may be less than 0.15.
[0015] (4) In the sintered body of (3), the compound may be Co 22 B4C2、W2Co 21 At least any one of B6, W2Co2B6 and CoWB.
[0016] (5) In the sintered body of (3) or (4) above, a value obtained by dividing the peak intensity of the compound by the peak intensity of diamond when subjected to X-ray diffraction may be 0.01 to 0.15.
[0017] (6) In the sintered body of (1) to (5) above, the resistivity measured in a state where the binder is removed may be 3.0 Ω·cm or less.
[0018] According to the sintered body of the above (6), when used for a cutting tool, the generation of friction plasma can be suppressed.
[0019] (7) In the sintered body of (1) to (6), the average particle size of the diamond particles may be 0.5 μm or more and 50 μm or less. The proportion of the diamond particles in the sintered body may be 80 volume percent or more and 99 volume percent or less.
[0020] (8) In the sintered bodies of (1) to (7), the bonding material may include at least one selected from the group consisting of elemental metals, alloys, and intermetallic compounds. The elemental metals, alloys, and intermetallic compounds may include at least one metal element selected from the group consisting of elements of Group IV of the periodic table, elements of Group V of the periodic table, elements of Group VI of the periodic table, iron, aluminum, silicon, cobalt, and nickel.
[0021] (9) In the sintered body of (1) to (8) above, the binder may contain at least cobalt.
[0022] (10) A cutting tool according to one embodiment includes a cutting edge portion. The cutting edge portion is formed of the sintered body according to (1) to (9) above.
[0023] According to the cutting tool of the above (10), the tool life can be improved.
[0024] [Details of the embodiments of the present disclosure] The details of the embodiments of the present disclosure will be described with reference to the accompanying drawings. In the following drawings, the same or corresponding parts are denoted by the same reference numerals, and repeated description will not be repeated.
[0025] The cutting tool involved in the embodiment is, for example, a cutting insert 100. The cutting tool involved in the embodiment is not limited to the cutting insert 100, but the cutting insert 100 is described below as an example of the cutting tool involved in the embodiment. Other examples of the cutting tool involved in the embodiment include a drill, an end mill, a wear-resistant tool, and the like.
[0026] (Configuration of Cutting Tool According to Embodiment) The structure of the cutting insert 100 will be described.
[0027] <General Configuration of Cutting Insert 100> Figure 1 is a top view of the cutting insert 100 . Figure 2 1 is a perspective view of the cutting insert 100. Figure 1 as well as Figure 2 As shown, the cutting insert 100 has a base material 10 and a blade tip portion 20. The cutting insert 100 is a polygonal shape (e.g., a triangular shape) when viewed from above. The polygonal shape (triangular shape) may not be a strict polygonal shape (triangular shape). More specifically, the corner of the cutting insert 100 when viewed from above may also be rounded.
[0028] The substrate 10 is in a polygonal shape (e.g., a triangular shape) when viewed from above. The substrate 10 has a top surface 10a, a bottom surface 10b, and a side surface 10c. The top surface 10a and the bottom surface 10b are end surfaces in the thickness direction of the substrate 10. The bottom surface 10b is the opposite surface of the top surface 10a in the thickness direction of the substrate 10. The side surface 10c is a surface connected to the top surface 10a and the bottom surface 10b.
[0029] The top surface 10a has a mounting portion 10d. The mounting portion 10d is located at a corner of the top surface 10a when viewed from above. The distance between the top surface 10a and the bottom surface 10b in the mounting portion 10d is smaller than the distance between the top surface 10a and the bottom surface 10b outside the mounting portion 10d. That is, there is a step between the mounting portion 10d and the portion of the top surface 10a outside the mounting portion 10d.
[0030] A through hole 11 is formed in the substrate 10. The through hole 11 penetrates the substrate 10 in the thickness direction. The through hole 11 is formed in the center of the substrate 10 when viewed from above. The cutting insert 100 is used for cutting processing by, for example, inserting a fixing member (not shown) into the through hole 11 and fastening the fixing member to a tool holder (not shown). However, the through hole 11 may not be formed in the substrate 10.
[0031] The substrate 10 is formed of, for example, cemented carbide. Cemented carbide is a composite material formed by sintering carbide particles and a bonding material. The carbide particles are, for example, particles of tungsten carbide, titanium carbide, tantalum carbide, etc. The bonding material is, for example, cobalt, nickel, iron, etc. However, the substrate 10 may also be formed of a material other than cemented carbide.
[0032] The blade tip 20 is mounted on the mounting portion 10d. The blade tip 20 is mounted on the base material 10, for example, by brazing. The blade tip 20 has a rake face 20a, a flank face 20b, and a cutting edge 20c. The rake face 20a is connected to a portion of the top surface 10a other than the mounting portion 10d. The flank face 20b is connected to the side surface 10c. The cutting edge 20c is formed on the ridgeline between the rake face 20a and the flank face 20b. A backing metal 21 may also be arranged on the bottom surface of the blade tip 20 (the opposite side of the rake face 20a). The backing metal 21 is formed, for example, of cemented carbide.
[0033] <Detailed Structure of Sintered Body Constituting Blade Tip 20> The blade tip 20 is formed by a sintered body containing diamond particles and a bonding material. The average particle size of the diamond particles in the sintered body constituting the blade tip 20 is preferably 0.5 μm or more and 50 μm or less. The proportion (volume ratio) of the diamond particles in the sintered body constituting the blade tip 20 is preferably 80 volume percent or more and 99 volume percent or less. The bonding material, for example, contains cobalt. In addition to cobalt, the bonding material may also contain tungsten and titanium. The component with the largest content in the bonding material is preferably cobalt.
[0034] The average grain size of the diamond grains in the sintered body constituting the blade tip portion 20 is calculated by the following method.
[0035] In calculating the average particle size of diamond particles in the sintered body constituting the blade tip portion 20, first, a sample including a cross section is cut out from an arbitrary position of the blade tip portion 20. The sample is cut out using, for example, a focused ion beam device, a cross-section polisher device, or the like.
[0036] Second, the cross section of the cut sample is observed using a scanning electron microscope (SEM). Through this observation, a reflected electron image (hereinafter referred to as a "SEM image") in the cross section of the cut sample is obtained. In the observation using the SEM, the magnification is adjusted so that more than 100 diamond particles are included in the measurement field of view. SEM images are obtained at five locations in the cross section of the cut sample.
[0037] The third, by image processing to SEM image, obtain the distribution of the particle diameter of the diamond particles included in the measurement visual field.The distribution of the particle diameter of this diamond particle is the distribution of number basis.This image processing for example uses Win ROOF ver.7.4.5, WinROOF2018 etc. that Sangu Shoji Co., Ltd. makes to carry out.The particle diameter of each diamond particle is obtained by calculating the equivalent circle diameter according to the area of each diamond particle obtained as the result of image processing.In addition, when obtaining the distribution of the particle diameter of diamond particles, do not consider the diamond particles that a part is in the measurement visual field outside.
[0038] Fourth, the median diameter of the diamond particles contained in the measurement field of view is determined based on the particle size distribution of the diamond particles contained in the measurement field of view obtained as described above. The value obtained by averaging the determined median diameters for five SEM images is regarded as the average diameter of the diamond particles in the sintered body constituting the blade tip portion 20.
[0039] The ratio of diamond particles in the sintered body constituting the blade tip portion 20 is calculated by the following method. In calculating the ratio of diamond particles in the sintered body constituting the blade tip portion 20, first, a sample including a cross section is cut out from an arbitrary position of the blade tip portion 20. The cutting of the sample is performed using, for example, a focused ion beam device, a cross-section polisher device, or the like.
[0040] Second, the cross section of the cut sample is observed by SEM. Through this observation, an SEM image of the cross section of the cut sample is obtained. In the observation using SEM, the magnification is adjusted to include more than 100 diamond particles in the measurement field of view. SEM images are obtained at five locations in the cross section of the cut sample.
[0041] Third, by image processing the SEM image, the ratio of the diamond particles contained in the measurement field of view is calculated. This image processing is performed by, for example, using Win ROOF ver.7.4.5, WinROOF2018 manufactured by Mitani Shoji Co., Ltd. to perform a binarization process on the SEM image. The dark field in the SEM image after the binarization process corresponds to the region where the diamond particles are present. The value obtained by dividing the area of the dark field by the area of the measurement region is regarded as the volume ratio of the diamond particles in the sintered body constituting the tip of the blade 20.
[0042] The boron concentration in the diamond particles is 0.001 mass percent or more and 0.1 mass percent or less. The boron concentration in the bonding material is 0.01 mass percent or more and 0.5 mass percent or less. The boron concentration in the bonding material is preferably greater than the boron concentration in the diamond particles (i.e., the value obtained by subtracting the boron concentration in the diamond particles from the boron concentration in the bonding material is preferably greater than 0 mass percent). The boron concentration in the bonding material may be 0.05 mass percent or more and 0.5 mass percent or less.
[0043] The boron concentration in the diamond particles and the boron concentration in the bonding material were measured by the following method.
[0044] In the measurement of the boron concentration in the diamond particles and the boron concentration in the bonding material, first, a sample is cut out from an arbitrary position of the blade tip 20. Second, the cut sample is subjected to an acid treatment. Through the acid treatment, the components of the bonding material contained in the sample are substantially all dissolved in the acid. That is, the sample after the acid treatment is substantially composed of only diamond particles.
[0045] The acid treatment is performed using a fluorine nitric acid aqueous solution. The fluorine nitric acid aqueous solution is prepared by mixing a 50% aqueous solution of hydrogen fluoride and a 60% aqueous solution of nitric acid at a ratio of 1:1. The acid treatment is performed by immersing the sample in the fluorine nitric acid aqueous solution and maintaining it at 200°C for 48 hours.
[0046] Third, the boron concentration in the diamond particles was measured by glow discharge mass spectrometry analysis of the acid-treated samples, and the boron concentration in the binder was measured by inductively coupled plasma analysis of the acid used in the acid treatment.
[0047] Compounds may also be precipitated in the combination. The compound precipitated in the combination contains at least two or more of cobalt, boron and carbon. For example, the compound precipitated in the combination is Co 22 B4C2、W2Co 21At least any one of B6, W2Co2B6 and CoWB.
[0048] The value obtained by dividing the peak intensity of the compound by the peak intensity of diamond when the sintered body constituting the blade tip portion 20 is subjected to X-ray diffraction is, for example, 0.15 or less. The value obtained by dividing the peak intensity of the compound by the peak intensity of diamond when the sintered body constituting the blade tip portion 20 is subjected to X-ray diffraction is preferably 0.01 or more and 0.15 or less. In addition, the value obtained by dividing the peak intensity of the compound by the peak intensity of diamond when the sintered body constituting the blade tip portion 20 is subjected to X-ray diffraction is, for example, greater than 0.
[0049] The value obtained by dividing the peak intensity of the compound by the peak intensity of diamond when the sintered body constituting the blade tip 20 is subjected to X-ray diffraction is measured by the following method. First, a sample including a cross section is cut out from any position of the blade tip 20. The cutting of the sample is performed, for example, using a focused ion beam device, a cross-section polishing machine device, etc. Second, in the above-mentioned cross section, the composition of the diamond particles and the bonding material is determined by the X-ray diffraction method. Third, in the above-mentioned cross section, an X-ray diffraction pattern is obtained by analyzing using the X-ray diffraction method. The analysis based on the X-ray diffraction method is performed by the θ-2θ method using the characteristic X-rays of Cu-Kα rays with a wavelength of 1.54 angstroms, the tube voltage of 40 kV, the tube current of 15 mA, the filter of a multilayer mirror, and the optical system of the concentration method.
[0050] Fourth, based on the above-mentioned X-ray diffraction pattern and the composition of the above-mentioned diamond particles and the bonding material, the peak intensity (peak height, cps) derived from each component is obtained. The peak intensity is obtained using the first peak of each component. Fifth, by dividing the total peak intensity of the compound in the bonding material obtained as described above by the total peak of diamond, a value obtained by dividing the peak intensity of the compound when the sintered body constituting the blade tip portion 20 is subjected to X-ray diffraction by the peak intensity of diamond is obtained.
[0051] The resistivity of the sintered body constituting the blade tip 20 after the binding material is removed is preferably greater than 3.0Ω·cm. The removal of the binding material is performed by the same acid treatment as when measuring the boron concentration in the diamond particles. The resistivity of the sintered body is measured by a four-terminal method. The resistivity of the sintered body is measured using a 182SENSITIVE DIGITAL VOLTMETER manufactured by KEITHLEY as a measuring device, under the conditions of a measuring temperature of 22°C, a measuring humidity of 60%, and an electrode spacing of 0.5mm. As the probe of the measuring device, a four-probe probe manufactured by NTT Advance Technology is used. A sample of 3mm×1mm×6mm is cut out from the sintered body constituting the blade tip 20 for the measurement of the resistivity.
[0052] The diamond powder prepared in the powder preparation step S1 does not contain boron, and boron is introduced into the diamond particles in the sintering step S3, so boron is biased to be present near the surface of the diamond particles. Therefore, if the boron concentration in the diamond particles is the same, the resistivity of the sintered body constituting the blade tip portion 20 after the binder is removed becomes smaller than the resistivity of the sintered body obtained by sintering the diamond powder doped with boron in advance.
[0053] <Method for Manufacturing Sintered Body Constituting Blade Tip 20> Figure 3 FIG. 2 is a process diagram showing a method for manufacturing a sintered body constituting the blade tip portion 20. Figure 3 As shown, the method for manufacturing the sintered body constituting the blade tip portion 20 includes a powder preparation step S1 , a powder mixing step S2 , and a sintering step S3 .
[0054] In the powder preparation step S1, diamond powder, bonding material powder and boron addition powder are prepared. Diamond powder is a powder of diamond, and bonding material powder is a powder formed of a material constituting the bonding material. Boron addition powder is a powder of boron or boron oxide. The ratio of diamond powder, bonding material powder and boron addition powder is appropriately selected according to the volume ratio of diamond particles in the sintered body constituting the blade tip portion 20 and the boron concentration in the diamond particles and the bonding material.
[0055] The powder mixing step S2 is divided into, for example, a first step and a second step performed after the first step. In the first step, the boron-added powder is crushed. The crushing of the boron-added powder is performed, for example, in a manner such that the average particle size of the boron-added powder is less than 5 μm. The crushing of the boron-added powder can also be performed after the diamond powder and the bonding material powder are mixed with the boron-added powder. The crushing of the boron-added powder is preferably performed in a manner such that the average particle size of the boron-added powder is less than 0.5 μm. The average particle size of the boron-added powder is measured, for example, by a particle size distribution measuring device such as Microtrac. The smaller the average particle size of the crushed boron-added powder, the easier it is to introduce boron into the diamond particles in the sintering step S3. In the second step, the diamond powder, the bonding material powder and the crushed boron-added powder are mixed. The mixing is performed using, for example, a grinding mill or a ball mill. However, the mixing method is not limited to this. Hereinafter, the powder formed by mixing the diamond powder, the bonding material powder and the boron-added powder is referred to as "mixed powder".
[0056] In the sintering step S3, the mixed powder is sintered. The sintering is performed by placing the mixed powder in a container and maintaining the mixed powder at a predetermined sintering temperature under a predetermined sintering pressure. In order to prevent impurities from being mixed into the mixed powder (sintered body), the container is formed of a high melting point metal such as tantalum and niobium. The sintering temperature can be appropriately selected according to the boron concentration in the diamond particles and the boron concentration in the bonding material. The sintering temperature is, for example, above 1500°C and below 1700°C. In addition, the higher the sintering temperature, the easier it is for boron to diffuse into the diamond particles, but if the sintering temperature is too high, the graphitization of the diamond is easy to proceed, and the strength of the bonding material is reduced. The sintering pressure is, for example, above 4.5GPa and above 6.5GPa. The holding time is, for example, above 40 minutes and less than 60 minutes.
[0057] (Effects of the Cutting Tool According to the Embodiment) Next, the effects of the cutting insert 100 will be described.
[0058] By making boron exist in diamond particles, the oxidation resistance of diamond particles can be improved, and as a result, the wear resistance of the blade tip portion 20 can be improved. According to the insights found by the inventors of the present invention, when the boron concentration in the diamond particles is less than 0.001 mass percent, the improvement effect of the oxidation resistance of the diamond particles based on boron is lacking. On the other hand, if the boron concentration in the diamond particles is greater than 0.1 mass percent, the amount of boron in the diamond particles is excessive, the hardness of the diamond particles is reduced, and the wear resistance of the blade tip portion 20 is reduced instead.
[0059] In the sintering step S3, the bonding material powder is melted, and the boron-added powder is dissolved in the molten bonding material. Moreover, a portion of the diamond powder is dissolved in the molten bonding material, and the diamond particles are precipitated again, thereby performing bonding (necking) between the diamond particles. The boron in the dissolved bonding material acts as a sintering aid, so when the boron concentration in the bonding material is less than 0.01 mass percent, it is difficult to produce necking between the diamond particles. In addition, according to the insights discovered by the inventors of the present invention, when the boron concentration in the bonding material is greater than 0.5 mass percent, compounds containing cobalt, boron, carbon, etc. are easily precipitated in the bonding material. The compounds in the bonding material reduce the strength of the bonding material and reduce the wear resistance.
[0060] In the cutting insert 100, the boron concentration in the diamond particles contained in the sintered body constituting the blade tip portion 20 is 0.001 mass percent or more and 0.1 mass percent or less, thereby improving the oxidation resistance of the diamond particles while maintaining the hardness of the diamond particles. In the cutting insert 100, the boron concentration in the bonding material contained in the sintered body constituting the blade tip portion 20 is 0.01 mass percent or more and 0.5 mass percent or less, thereby ensuring the neck growth strength between the diamond particles and ensuring the strength of the bonding material. In this way, according to the cutting insert 100, the wear resistance of the blade tip portion 20 can be improved.
[0061] When the average particle size of the diamond particles in the sintered body constituting the blade tip portion 20 is less than 0.5 μm, the surface area of the diamond particles becomes large, so the surface oxidation of the diamond particles is easy to proceed. When the average particle size of the diamond particles in the sintered body constituting the blade tip portion 20 is greater than 50 μm, the toughness of the sintered body constituting the blade tip portion 20 is reduced, and defects are easily generated. Therefore, by setting the average particle size of the diamond particles in the sintered body constituting the blade tip portion 20 to be greater than 0.5 μm and less than 50 μm, the wear resistance of the blade tip portion 20 can be further improved.
[0062] When the ratio of diamond particles in the sintered body constituting the blade tip portion 20 is less than 80 volume percent, the hardness of the blade tip portion 20 decreases. Therefore, by setting the ratio of diamond particles in the sintered body constituting the blade tip portion 20 to 80 volume percent or more and 99 volume percent or less, the wear resistance of the blade tip portion 20 can be further improved.
[0063] When the blade tip 20 is charged due to contact between the blade tip 20 and the workpiece, friction plasma is sometimes generated between the blade tip 20 and the workpiece, and wear of the blade tip 20 is likely to proceed. When the resistivity of the sintered body constituting the blade tip 20 measured after the binder is removed is 3.0Ω·cm or less, the blade tip 20 is not easily charged due to contact with the workpiece, and the wear of the blade tip 20 caused by the generation of friction plasma can be suppressed.
[0064] (Example) In order to evaluate the relationship between the particle size of the boron-added powder prepared in the powder preparation step S1 and the boron concentration in the binder contained in the sintered body constituting the blade tip portion 20, sample 1 and sample 2 were prepared as samples of the sintered body. As shown in Table 1, the ratio of the mass of the boron-added powder to the mass of the binder powder (the value obtained by dividing the mass of the boron-added powder by the mass of the binder powder), the sintering pressure, the sintering temperature, and the sintering time were the same in sample 1 and sample 2. However, in sample 1, the average particle size of the boron-added powder was 5 μm or less, while in sample 2, the average particle size of the boron-added powder was greater than 5 μm.
[0065]
[0066] As shown in Table 1, in Sample 1, the boron concentration in the bonding material is within the range of 0.01 mass percent to 0.5 mass percent. In Sample 2, the boron concentration in the bonding material is not within the range of 0.01 mass percent to 0.5 mass percent. In addition, in Sample 1 and Sample 2, the boron concentration in the diamond particles is within the range of 0.001 mass percent to 0.1 mass percent. From this comparison, it can be seen that by making the average particle size of the boron-added powder less than 5 μm, the boron concentration in the bonding material can be made 0.01 mass percent to 0.5 mass percent.
[0067] In order to evaluate the relationship between the boron concentration in the diamond grains and the bonding material contained in the sintered body constituting the blade tip portion 20 and the wear resistance of the blade tip portion 20, samples 3 to 24 were prepared as sintered body samples. In samples 3 to 24, as shown in Table 2, the boron concentration in the diamond grains and the bonding material contained in the sintered body constituting the blade tip portion 20 changed.
[0068]
[0069] The boron concentration in the diamond particles was 0.001 mass percent or more and 0.1 mass percent or more as condition A, and the boron concentration in the bonding material was 0.01 mass percent or more and 0.1 mass percent or less as condition B. Samples 3 to 18 satisfied both condition A and condition B. Samples 19 to 24 did not satisfy at least one of condition A and condition B.
[0070] In order to conduct the cutting test, a cutting insert having a blade tip portion 20 formed by using samples 3 to 24 was prepared. The cutting insert has a shape corresponding to the cutting insert SNEW1204ADFR manufactured by Sumitomo Electric Hardmetal Co., Ltd. In addition, the cutting insert was mounted on the retaining member RF4160R manufactured by Sumitomo Electric Hardmetal Co., Ltd. and then provided for milling. The milling was performed with a feed rate of 0.2 mm / t and a cut-in amount of 0.6 mm. The cutting was dry processing without supplying a coolant. The size of the workpiece provided for the cutting was 90 mm × 90 mm × 90 mm, and the material of the workpiece provided for the cutting was a resin containing glass. In the cutting test, the number of passes that could be processed until the average back face wear reached 250 μm was evaluated.
[0071]
[0072] As shown in Table 3, in the cutting inserts in which the cutting edge portion 20 is formed using samples 3 to 18, the number of passes that can be processed is increased compared to the cutting inserts in which the cutting edge portion 20 is formed using samples 19 to 24. As described above, in samples 3 to 18, both conditions A and conditions B are satisfied, while in samples 19 to 24, at least one of conditions A and conditions B is not satisfied. From this comparison, it can be seen that by satisfying both conditions A and conditions B, the wear resistance of the cutting edge portion 20 can be improved.
[0073] The average particle size of the diamond particles was 0.5 μm or more and 50 μm or less as condition C. The ratio of the diamond particles in the sintered body was 80 volume percent or more and 99 volume percent or less as condition D. In samples 3 to 15, in addition to conditions A and B, conditions C and D were also satisfied. In samples 16 to 18, although conditions A and B were satisfied, neither condition C nor condition D was satisfied.
[0074] In addition, in the cutting inserts formed with the cutting edge portion 20 using samples 3 to 15, the number of passes that can be processed is greater than that of the cutting inserts formed with the cutting edge portion 20 using samples 16 to 18. From this comparison, it is understood that by further satisfying conditions C and D, the wear resistance of the cutting edge portion 20 can be further improved.
[0075] Table 3 also shows the value obtained by dividing the peak intensity of the compound by the peak intensity of diamond when performing X-ray diffraction. In samples 3 to 18, the value obtained by dividing the peak intensity of the compound by the peak intensity of diamond when performing X-ray diffraction is 0.15 or less. In samples 20 and 21 in which the boron concentration in the bonding material is greater than 0.5 mass percent, the value obtained by dividing the peak intensity of the compound by the peak intensity of diamond when performing X-ray diffraction is greater than 0.15. It can be seen that by setting the boron concentration in the bonding material to less than 0.5 mass percent, the value obtained by dividing the peak intensity of the compound by the peak intensity of diamond when performing X-ray diffraction is 0.15 or less, that is, the precipitation of the compound in the bonding material can be suppressed.
[0076] In order to evaluate the effect of the diamond powder pre-doped with boron on the resistivity of the sintered body after the binder was removed, samples 25 and 26 were prepared as sintered body samples. As shown in Table 4, the boron concentration in the diamond particles and the boron concentration in the binder were the same in samples 25 and 26. Sample 25 was formed using diamond powder not doped with boron. In sample 26, half of the diamond powder was pre-doped with boron.
[0077]
[0078] As shown in Table 5, in Sample 25, the resistivity of the sintered body after the binder was removed was within the range of 3.0 Ω·cm or less. On the other hand, in Sample 26, the resistivity of the sintered body after the binder was removed was greater than 3.0 Ω·cm. From this comparison, it can be seen that when the diamond powder is not pre-doped with boron, even if the boron concentration in the diamond particles is the same, boron is preferentially present on the surface of the diamond particles, which can improve the resistivity of the sintered body after the binder is removed.
[0079]
[0080] (Variation) In the above description, the case where the binder contained in the sintered body constituting the blade tip portion 20 is cobalt is described as an example, but the binder contained in the sintered body constituting the blade tip portion 20 is not limited to cobalt.
[0081] The bonding material contained in the sintered body constituting the blade tip portion 20 may include at least one selected from the group consisting of a single metal, an alloy, and an intermetallic compound. The single metal, alloy, and intermetallic compound include at least one metal element selected from the group consisting of a fourth group element of the periodic table (e.g., titanium, zirconium, and hafnium), a fifth group element of the periodic table (e.g., vanadium, tantalum, and niobium), a sixth group element of the periodic table (e.g., chromium, molybdenum, and tungsten), aluminum, iron, silicon, cobalt, and nickel. The above-mentioned periodic table is a so-called long-period type periodic table.
[0082] In the above description, the case where the cutting insert 100 includes the base material 10 is described, but a portion other than the cutting edge portion 20 of the cutting insert 100 may be formed of the same sintered body as the cutting edge portion 20 .
[0083] The embodiments disclosed this time should be considered as illustrative in all aspects and not restrictive. The scope of the present invention is indicated by the claims rather than the embodiments described above, and is intended to include all modifications within the meaning and scope equivalent to the claims.
[0084] Description of Reference Numerals 10: substrate; 10a: top surface; 10b: bottom surface; 10c: side surface; 10d: mounting portion; 11: through hole; 20: tip portion; 20a: front cutting surface; 20b: back cutting surface; 20c: cutting edge; 21: backing metal; 100: cutting blade; S1: powder preparation process; S2: powder mixing process; S3: sintering process.
Claims
1. A sintered body, wherein: The sintered body comprises diamond particles and a bonding material. The boron concentration in the diamond particles is greater than or equal to 0.001 mass percent and less than or equal to 0.1 mass percent, The boron concentration in the bonding material is greater than or equal to 0.01 mass percent and less than or equal to 0.5 mass percent.
2. The sintered body according to claim 1, wherein The boron concentration in the bonding material is greater than or equal to 0.05 mass percent and less than or equal to 0.5 mass percent.
3. The sintered body according to claim 2, wherein The sintered body further comprises a compound precipitated in the binding material, The compound contains at least two or more of cobalt, boron and carbon, The value obtained by dividing the peak intensity of the compound by the peak intensity of diamond when performing X-ray diffraction is 0.15 or less.
4. The sintered body according to claim 3, wherein The compound is Co 22 B4C2、W2Co 21 At least any one of B6, W2Co2B6 and CoWB.
5. The sintered body according to claim 3 or 4, wherein The value obtained by dividing the peak intensity of the compound by the peak intensity of diamond when performing X-ray diffraction is 0.01 or more and 0.15 or less.
6. The sintered body according to any one of claims 1 to 5, wherein The resistivity measured in a state where the bonding material is removed is 3.0 Ω·cm or less.
7. The sintered body according to any one of claims 1 to 6, wherein The average particle size of the diamond particles is greater than or equal to 0.5 μm and less than or equal to 50 μm. The ratio of the diamond particles in the sintered body is 80 volume percent or more and 99 volume percent or less.
8. The sintered body according to any one of claims 1 to 7, wherein The bonding material comprises at least one selected from the group consisting of a single metal, an alloy, and an intermetallic compound. The elemental metal, the alloy, and the intermetallic compound include at least one metal element selected from the group consisting of Group IV elements of the periodic table, Group V elements of the periodic table, Group VI elements of the periodic table, iron, aluminum, silicon, cobalt, and nickel.
9. The sintered body according to any one of claims 1 to 8, wherein The bonding material contains at least cobalt.
10. A cutting tool, wherein: The cutting tool comprises a cutting edge portion, The blade tip portion is formed of the sintered body according to any one of claims 1 to 9.
Citation Information
Patent Citations
Sintered body and cutting tool
CN116529004A
Surface enriched diamond
EP0892092A1
Production of abrasion resistant hard metal body
JP1978124102A
High-hardness, electrically conductive polycrystalline diamond and method for producing the same
JP2012066979A
Diamond sintered compact and method for producing the same
JP2012140256A
